(untitled) (Bangladesh Veterinarian, 2013)
To determine the in vitro effects of environmental and nutritional factors on the development and hatching of eggs of Haemonchus contortus, eggs were cultivated at different temperatures, humidity and pH, in phosphate buffered saline (PBS), tap water, or normal saline, with and without faecal material and soil. No development of eggs occurred at 4ºC up to 15 days. Hatching was maximum (40.7%) at 30ºC on Day 5. Maximum hatching (39.5%) was observed on Day 6 at pH 6 and hatching was minimum (3.3%) on Day 4 at pH 3. Hatching did not occur at pH 2. At a relative humidity of 80 - 90%, maximum hatching (42.2%) was recorded on Day 5. Light had no effect on development and hatching. Maximum proportion of eggs hatched in PBS containing faecal material (40.1%). It is suggested that PBS containing faecal material may be used for the incubation of eggs of Haemonchus contortus. Best results may be obtained at 30ºC, pH 6 and relative humidity 80 - 90%. DOI: http://dx.doi.org/10.3329/bvet.v30i1.16279 Bangl. vet. 2013. Vol. 30, No. 1, 1-9